الأصوات عند الخليل بن أحمد الفراهيدي: Sounds according to Khalil ibn Ahmad Al-Farahidi - Rahmawati, Fitra Awalia; Zidni, Salma Izza (SIBAWAYH Arabic Language and Education, 2021)
تستند هذه الدراسة إلى عدد من المنطلقات عن نظرية الأصوات عند الخليل بن أحمد الفراهيدي. مصدر الصوت من انتقل الهواء الخارجي على شكل موجات حتى تصل إلى الأذن الإنسانية، فالسمع هو الحاسة الطبيعية لفهم الصوت. واستطاع الإنسان لإدراك الصوتية التي نسميها كلاما. عند علماء العربية أن الخليل أول مؤلف قاموسا عربيا يسمى "كتاب العين" الذي يدرس أصوات اللغة كوحدة صوتية ووحدات كلمات موصوفة في مقدمة كتابه. أما الغرض من هذا البحث فهو معرفة تفكيره في الأصوات. وهذا  البحث من نوع الدراسة المكتبية بجمع البيانات من الكتب والمصادر الأخرى  المتعلقة بالبحث. وفي تحليل بحثها استخدمت الباحثة المنهج التحليلي الوصفي فحص البحث العلمي من الحقائق بالمنهج الوصفي والمنظمة. وخطوات إجراء هذا البحث هي جمع البيانات، وتصنيفها، ومعالجتها، وبيانها. وكشفت الدراسة النتائج الآتية أن الخليل بن أحمد الفراهيدي يصف عن الأصوات وهو 1) مخرج الصوت 2) صفات الصوت 3) الجهر والهمس. وبعد أن تم كتابة هذا البحث، تقترح الباحثة إلى متعلم اللغة العربية خاصة في دراسة علم الأصوات لبحث المراجع الموثوقة لسهولة الفهم والتعليم بطريقة بسيطة. وترجى هذا البحث يساعد في توسيع المعلومات والمعرفات ويكون مرجعا للباحثين المستقبل لأن اعترفت الباحثة بأن هذا البحث جزء صغير من نظرية الخليل بن أحمد الفراهيدي. لذلك ترجى للقارئين والباحثين المستقبل ليكون أكمل من ذي قبل.This study is based on a number of starting points from the theory of sounds according to Khalil bin Ahmed Al-Farahidi. The source of the sound is from the outside air moving in the form of waves until it reaches the human ear, so hearing is the natural sense of understanding the sound. And people was able to perceive the phoneme that we call speech. According to Arabic scholars, Khalil was the first to author an Arabic dictionary called "Kitab al-Ain", which studies the sounds of language as a unit of phoneme and word units described in the introduction to his book. The purpose of this research is to know his thinking about sounds. This research is of the type of a desk study by collecting data from books and other sources related to the research. In analyzing her research, the researcher used the analytical and descriptive method to examine scientific research from facts with a descriptive and structured approach. The steps for conducting this research are data collection, classification, processing, and statement. The study revealed the following results that Al-Khalil bin Ahmad Al-Farahidi describes voices, which is 1) the sound output 2) the qualities of the sound 3) the loudness and the whisper. After this research has been written, the researcher proposes to the Arabic language learner, especially in studying phonology, to search for reliable references for ease of understanding and education in a simple way. The hope of this research will help in expanding the information and identifiers and be a reference for future researchers because the researcher admitted that this research is a small part of the theory of Al Khalil bin Ahmed Al Farahidi. Therefore, readers and researchers aspired to the future to be more complete than before.Keyword: Al-Aswat, Khalil ibn Ahmad Al-Farahidi